Social psychology - Myers, David G.; Twenge, Jean M. 1971- (McGraw Hill LLC, 2022)
"We cast social psychology in the intellectual tradition of the liberal arts. By the teaching of great literature, philosophy, and science, liberal arts education seeks to expand our awareness and to liberate us from the confines of the present. By focusing on humanly significant issues, we aim to offer social psychology's big ideas and findings to pre-professional psychology students, and to do so in ways that stimulate all students. And with close-up looks at how the game is played-at the varied research tools that reveal the workings of our social nature-we hope to enable students to think smarter"--Provided by publisher.